QSAR rationales for the 1,2-diarylcyclopentenes as prostaglandin EP1 receptor antagonists: Potentially useful in the treatment of inflammatory pain - Sharma, Brij Kishore; Pilania, Pradeep; Singh, Prithvi (European Journal of Chemistry, 2010)
The EP1 receptor inhibitory activity of 1,2-diarylcyclopentene derivatives have been quantitatively analyzed in terms of Dragon descriptors. The derived QSAR models have provided rationales to explain the EP1 receptor inhibitory activity of 1,2-diarylcyclopentene derivatives. The 2D-autocorrelation descriptors (MATS4e, MATS5e, MATS7v, GATS5e and GATS7v) have highlighted the role of atomic properties in respective lags of autocorrelations to explain the biological actions of 1,2-diarylcyclopentene analogues. Presence of fluorine atom (nF) and smaller distance between N and O atoms (T(N..O)) in molecular structures, in addition to Kier-Hall electrotopological states (Ss) have also shown prevalence to optimize the EP1 receptor inhibitory activity. Partial least square analysis has confirmed the dominance of information content of the combinatorial protocol in multiple linear regression identified descriptors. Applicability domain analysis revealed that the suggested model matches the high quality parameters with good fitting power and capability of assessing external data. All the compounds are within the applicability domain of the proposed model and were evaluated correctly.